Effect of Water and Chemical Spray on Quality Parameters TM, Ash, and CV of E4700 Product Coal at PT Adaro Indonesia Site Kelanis, South Barito Regency, Central Kalimantan - Rinaldi Suntana; Heri Prabowo (Departemen Teknik Pertambangan FT UNP, 2024)
PT Adaro Indonesia is a coal producer that produces several types of coal using standard doses. However, to improve the quality of E4700 coal, the company needs to examine the effect of chemical use on coal quality. This study aims to determine the effect of the use of dust suppressant chemicals on the value of coal quality parameters, identify variables that have a significant effect on the calorific value of coal, and analyze the concentration level of chemicals that have a significant effect on changes in the value of quality parameters in E4700 coal. Based on the analysis, after spraying with chemicals, there is a change in the value of coal quality parameters. When using a chemical concentration of 25 ppm, there was a change in the value of Total Moisture by -0.62%, Ash by -0.04%, and calories (CV) by 47 cal/g. At a concentration of 35 ppm, the Total Moisture value changed by -1.58%, Ash by -0.16%, and calories (CV) by 117 cal/g. And at 50 ppm concentration, there was a change in Total Moisture value of -1.96%, Ash of -0.24%, and calories (CV) of 142 cal/g. These results indicate that the use of chemicals affects the quality of E4700 coal. This study also used multiple linear regression statistical tests to obtain the significance value of the Total Moisture variable.